LEGAL REFORM IN ADDRESSING SEXUAL VIOLENCE IN INDONESIA: AN ANALYSIS OF THE IMPLEMENTATION OF LAW NO. 12 OF 2022 ON SEXUAL VIOLENCE CRIMES - Susilowati, Christina Maya Indah; Frans, Mardian Putra (Revista Direito e Sexualidade, 2024)
This study examines the transformative impact of Indonesia’s Law No. 12 of 2022 on Sexual Violence Crimes, which replaced outdated provisions within the Indonesian Criminal Code. The new law addresses the complexities of sexual violence by expanding the definition beyond physical assault to include psychological manipulation and exploitation of power, authority, and trust. Previously, legal recognition of sexual violence was limited to instances involving physical force or threats, often overlooking abuses rooted in power dynamics. Advocacy by women’s organizations played a pivotal role in the enactment of this law, emphasizing a victim-centered approach. Key challenges persist, particularly in legally defining and applying concepts such as power imbalances and deception, which are crucial for prosecuting cases involving non-physical coercion. The legislation’s broader scope aligns with feminist perspectives on sexual violence as an issue intertwined with systemic gender inequalities. This research highlights the ongoing need for comprehensive legal frameworks, awareness, and institutional support to effectively address and mitigate sexual violence in Indonesia.